PENGARUH CR, DER, ROE, ROA, NPM, EPS, DAN PER TERHADAP HARGA SAHAM (Studi Kasus pada Perusahaan INDEKS LQ45 di BEI) (Faletehan Jurnal Ekonomi dan Bisnis, 2024)
This study aims to study the effect of CR. DER, ROE, ROA, NPM, EPS, and PER on stock prices. The data used in this study are secondary data obtained from other parties, namely the Indonesia Stock Exchange in the form of company financial statements. The sampling technique uses purposive sampling, namely 21 companies. The analysis technique used is the classical assumption test, the coefficient of determination (R2), multiple linear regression, and hypothesis testing (F test and t test). Based on the results of the analysis it can be concluded that CR, DER, ROE, ROA, NPM, EPS, and PER have a positive and significant effect on stock prices. While CR, DER, ROA and NPM determine the negative and significant effect on stock prices, while ROE, EPS and PER have a positive and significant effect on stock prices at LQ45 companies on the Indonesia Stock Exchange.